From prospectus to profit:a fundamental analysis on the IPO of WebCoats PLC. & NRB Bank Limited for investment decision - Mahmud, Tanvir (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2024.